Queueing Theory Study of Round Robin Versus Priority Dynamic Quantum Time Round Robin Scheduling Algorithms - Maysoon, A. Mohammed; Mazlina, Abdul Majid; Balsam, A. Mustafa; Rana, Fareed Ghani (IEEE, 2015)
The queue size distribution and average waiting time for a time-shared system using round-robin (RR) scheduling, with and without overhead, are determined. In this study, the incoming processes are prioritized, and dynamic quantum times are assigned depending on the level of priority. With these parameters, RR versus priority dynamic quantum time round robin scheduling algorithm is analyzed to explore the effect of changing the quantum time of processes and determine the optimum context switches, turnaround time, and waiting time.